The Mystical Legacy of Shah Niaz Ahmad Barelvi: A Comprehensive Study of His Life, works, and the Philosophy of Wahdat al-Wujūd - Razia Sultana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Hazrat Shah Niaz Ahmad Barelvi (1742–1834) was a distinguished Sufi saint, poet, and scholar of the Indian subcontinent, and the founder of the Niazi Sufi Order. Associated with the Chishti, Qadiri, Nizami, Sabri, and Naqshbandi orders, he played a vital role in preserving and transmitting the spiritual heritage of Sufism during the eighteenth century. His khanqah in Bareilly emerged as a beacon of spiritual enlightenment and religious tolerance, attracting seekers from diverse backgrounds, including Hindus and Muslims, from across the subcontinent and beyond. A prolific writer and poet, Shah Niaz authored numerous works in Arabic, Persian and Urdu covering both exoteric and esoteric sciences. His poetry, infused with themes of divine love (ishq) and Wahdat al-Wujud (Unity of Being), represents one of the finest expressions of mystical thought in South Asia. This article highlights his life, lineage, spiritual training, writings, and his unique contribution to Sufi philosophy and literature.